2013
DOI: 10.1002/ls.1234
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behaviour of anodic titanium oxide films produced by plasma electrolytic oxidation for dental implants

Abstract: Commercially pure Titanium (cp‐Ti) and its alloys are the materials most widely used for dental implant applications. In the present work, anodic oxide films have been produced on cp‐Ti surfaces by plasma electrolytic oxidation (PEO) technique. After PEO treatments, oxide films with different surface features (e.g. surface roughness, morphology and film thickness) were obtained according with anodising parameters. The tribocorrosion behaviour of untreated and PEO‐treated Ti samples was investigated by reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 24 publications
4
39
0
12
Order By: Relevance
“…PEO treatment was performed in two different aqueous electrolyte solutions: (1) a commercial electrolyte (CE) provided from Keronite (Keronite Electrolyte 1003-01 for titanium) composed of 0.1-1 % sodium fluoride (NaF) and other elements such as Ca and P; (2) a Ca/P-based electrolyte (Cβ) composed of 0.35 M of calcium acetate (calcium acetate hydrate, Scharlab, Spain) and 0.02 M of β-glycerol phosphate (β-glycerol phosphate disodium salt pentahydrate, Scharlab, Spain). In our previous work [59], the influence of PEO current density on anodic films features was investigated by PEO treatments carried out at 3 and 8 A/dm 2 for 10 min in CE electrolyte. In the present investigation, we aim to study the influence of PEO processing time and electrolyte composition on the characteristics of anodic films.…”
Section: Synthesis Of Ca-and P-enriched Ti Oxide Films By Peomentioning
confidence: 99%
See 2 more Smart Citations
“…PEO treatment was performed in two different aqueous electrolyte solutions: (1) a commercial electrolyte (CE) provided from Keronite (Keronite Electrolyte 1003-01 for titanium) composed of 0.1-1 % sodium fluoride (NaF) and other elements such as Ca and P; (2) a Ca/P-based electrolyte (Cβ) composed of 0.35 M of calcium acetate (calcium acetate hydrate, Scharlab, Spain) and 0.02 M of β-glycerol phosphate (β-glycerol phosphate disodium salt pentahydrate, Scharlab, Spain). In our previous work [59], the influence of PEO current density on anodic films features was investigated by PEO treatments carried out at 3 and 8 A/dm 2 for 10 min in CE electrolyte. In the present investigation, we aim to study the influence of PEO processing time and electrolyte composition on the characteristics of anodic films.…”
Section: Synthesis Of Ca-and P-enriched Ti Oxide Films By Peomentioning
confidence: 99%
“…This electrolyte was chosen once on one side, it has been generally used in previous research works [2,18,61,62,63] but also because the electrochemical behavior of metallic materials in Fusayama's saliva, its similar to the one observed in human saliva [64]. It is aimed to simulate the highly corrosive oral cavity environment with Cl − , F − , and H + ions playing a significant role on corrosion of dental implant materials [20].…”
Section: Tribocorrosion Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both displayed important levels of roughness consistent with previous work. 25 These similarities can be explained by the heterogeneity of the surface treatments. Although the anodic process was used to alter the surface composition but not the pore size and dispersion (these parameters were not controlled), the etching step was only applied to remove surface impurities.…”
Section: 24mentioning
confidence: 99%
“…While exact comparison of weight loss results was not possible with corresponding values reported in the literature, there are some observed similarities. Alves et al, for example, reported wear scar depth of 16.0 ± 5.66 lm for tribocorrosion on CP-Ti (similar density to that of Ti-V alloy) using a normal force of 2 N, artificial saliva of 37°C, alumina ball counter-body of 10 mm diameter, 3 mm displacement of 2 Hz and 720 s duration [58]. Licausi et al reported a weight loss of 384 lg for tribocorrosion of Ti-V alloy using alumina ball of diameter 6 mm, a load of 5 N, and artificial saliva of pH 6.0 and 37°C [53].…”
Section: Wear and Corrosion Lossmentioning
confidence: 99%